Memperkuat Generasi Muda Melalui Nilai-Nilai Pancasila Sebagai Upaya Berkepribadian Unggul dan Berkarakter Mulia - Ningtyas, Dina Nurayu; Kurnia, Heri; Sari, Tri Yunita; Lestari, Dian (Academy of Social Science and Global Citizenship Journal, 2022)
This article discusses the importance of strengthening the younger generation through the values of Pancasila as an effort to have superior personality and noble character. The method used in this article is through a literature review, the article identifies problems and challenges in implementing Pancasila education. Emphasis on developing superior personality and noble character is an important key in building a strong young generation. Pancasila education has an important role in shaping the younger generation who have a strong moral foundation, awareness of their rights and obligations as citizens, superior personality, noble character, and a positive attitude in facing global challenges. To strengthen the younger generation through the values of Pancasila, cooperation between the government, educational institutions, families and society as a whole is needed. Consistent implementation, improving the quality of teachers, providing adequate learning resources, and integrating Pancasila values into the education curriculum are important steps in achieving this goal. With continuous efforts, the younger generation will become the backbone of nation building with integrity, superior personality and noble character.